2016
DOI: 10.1038/srep34578
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) induces premature senescence through ROS-mediated p53 pathway in L-02 hepatocytes

Abstract: Hexavalent Chromium [Cr(VI)], which can be found of various uses in industries such as metallurgy and textile dying, can cause a number of human disease including inflammation and cancer. Unlike previous research that focused on Cr(VI)-induced oxidative damage and apoptosis, this study placed emphasis on premature senescence that can be induced by low-dose and long-term Cr(VI) exposure. We found Cr(VI) induced premature senescence in L-02 hepatocytes, as confirmed by increase in senescence associated-β-galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Cr(V) and Cr(IV)]. Moreover, Zhang, Zhang, Zhong and Xiao () found that Cr(VI) stabilized p53 through phosphorylation at Ser15 in L‐02 hepatocytes and increased expression of p53‐transcriptional target p21. The authors also found that Cr(VI) targeted and inhibited mitochondrial respiratory chain complex I and II to enhance ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Cr(V) and Cr(IV)]. Moreover, Zhang, Zhang, Zhong and Xiao () found that Cr(VI) stabilized p53 through phosphorylation at Ser15 in L‐02 hepatocytes and increased expression of p53‐transcriptional target p21. The authors also found that Cr(VI) targeted and inhibited mitochondrial respiratory chain complex I and II to enhance ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium-induced cytotoxicity affects essential micronutrient absorption, lipid peroxidation, cell cycle arrest and ultimate cell death in plants [8,22,56,87]. Toxic Cr levels also mediate the stomatal abnormalities, such as the decreased size of stomatal aperture, swelling of guard cells, changes in membrane permeability level, ion flux, and osmotic pressure [22,87,114,115]. These stomatal aberrations significantly influence the a, b, and total chlorophyll contents, stomatal conductance, photosynthetic rate, respiration, and transpiration rate [87,114,115].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 99%
“…Toxic Cr levels also mediate the stomatal abnormalities, such as the decreased size of stomatal aperture, swelling of guard cells, changes in membrane permeability level, ion flux, and osmotic pressure [22,87,114,115]. These stomatal aberrations significantly influence the a, b, and total chlorophyll contents, stomatal conductance, photosynthetic rate, respiration, and transpiration rate [87,114,115]. Trichomes, which are unicellular outgrowths on the leaf, play a defensive role in plants under stress conditions [116,117].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 99%
“…Hepatocytes were treated, harvested, washed with ice-cold PBS, and subjected to western blot analysis, as previously described [21]. Briefly, approximately 50 μg protein of each different treatment group was separated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and transferred to polyvinylidene fluoride (PVDF) membranes.…”
Section: Western Blot Analysis For Protein Levelsmentioning
confidence: 99%
“…Cell culture and drug treatment L-02 hepatocytes were cultured as previously described [21]. The stock solution of Cr(VI) was prepared with phosphate buffered solution (PBS).…”
mentioning
confidence: 99%